2000
DOI: 10.1590/s1517-83822000000100005
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant tuberculosis among male inmates in Rio de Janeiro, Brazil

Abstract: Susceptibility tests to six anti-tuberculosis drugs were performed on fifty-eight M. tuberculosis isolates obtained from tuberculous inmates in the Male Penal Sanatorium, Rio de Janeiro, Brazil. The rate of resistant tuberculosis was higher than that observed in the community. The overall resistance rate was 17.2% and 3.4% of the isolates were multi-drug resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
5
Order By: Relevance
“…Epidemiologic studies have shown that risk of TB increases with close contacts of sputum-smear-positive patients and that the prevalence of clinical disease among intimate contacts of TB cases is high [ 6 ]. Similarly, there are growing fears that the high rate of TB in prisons coupled with weak health care systems are contributing to the emergence of Multi-Drug Resistant Tuberculosis (MDRTB) strains [ 7 ]. This study therefore, sought to find out the prevalence of tuberculosis among prison inmates at Mbarara central prison, Kiswahili cell Mbarara District, South Western Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that risk of TB increases with close contacts of sputum-smear-positive patients and that the prevalence of clinical disease among intimate contacts of TB cases is high [ 6 ]. Similarly, there are growing fears that the high rate of TB in prisons coupled with weak health care systems are contributing to the emergence of Multi-Drug Resistant Tuberculosis (MDRTB) strains [ 7 ]. This study therefore, sought to find out the prevalence of tuberculosis among prison inmates at Mbarara central prison, Kiswahili cell Mbarara District, South Western Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…In a Taiwanese study; 19.0% of the strains were resistant to INH, 6.1% to RIF, 15.7% to EMB, and 10.0% to STM (21). In a Brazilian study 13.8% of the strains were resistant to INH and 8.6% for STM (22).…”
Section: Discussionmentioning
confidence: 96%
“…En nuestro trabajo, un alto porcentaje de resistencia a rifampicina solo se encontró en la población antes tratada. Además, entre los hallazgos de este estudio se evidenció que entre el 3,8% y el 8,9% de pacientes TB pulmonar, son resistentes a isoniacida y rifampicina juntas; es decir, La TB MDR, lo cual difiere del 4% de TB MDR en la población general de nuestra región para el mismo periodo de tiempo [23] . Se sabe que en las Américas el 3,5% de casos de TB que se diagnostican son casos de TB MDR y que a través de investigaciones preliminares realizadas en centros penitenciarios de algunos países, la presencia de TB MDR es más alta, debido básicamente al control inadecuado de casos de TB * Total = 245 pacientes, para los demás casos = 130.…”
Section: Discussionunclassified